PENGUATAN KETERLIBATAN AYAH DALAM PENCEGAHAN STUNTING MELALUI PSIKOEDUKASI BERBASIS KETERAMPILAN PADA KELOMPOK AYAH DI PADUKUHAN DKU, KALURAHAN CITRA, BANGUNTAPAN, YOGYAKARTA - Ida Ayu Nyoman Vidyawati (PT. Giat Konseling Nusantara, 2026)
Stunting remains one of the major public health problems in Indonesia and has long-term impacts on children's physical, cognitive, emotional development, as well as future productivity. Stunting prevention efforts have primarily focused on nutritional and health interventions, while psychosocial aspects and family parenting practices have received less attention. Initial assessment findings in Padukuhan DKU, Kalurahan Citra, indicated that fathers' involvement in parenting was still low, as reflected by limited participation in child health activities, low direct interaction with children, and limited involvement in decision-making related to parenting and child health. This community service program aimed to improve fathers' involvement in parenting through skill-based psychoeducation as an effort to prevent stunting. The method used was group psychoeducation combined with reflective discussions, motivational reinforcement, parenting skills training, and behavioral commitment activities. The participants consisted of fathers with toddlers living in Padukuhan DKU. Evaluation was conducted using a Behavioral Checklist based on Lamb’s theory of father involvement, which includes the dimensions of accessibility, engagement, and responsibility. The results showed an average increase of 24.6% in fathers’ involvement after the intervention. Improvements occurred in the dimensions of accessibility, engagement, and responsibility. The findings suggest that skill-based psychoeducation can serve as a preventive strategy to support stunting prevention through strengthening family parenting capacities.